Spinal Intramedullary Tuberculosis - Varghese, Prithvi; Abdul Jalal, Muhammed Jasim; Kandathil, Julio Chacko; Mathew, Iona Leekha (The Surgery Journal, 2017)
Tuberculosis of the central nervous system accounts for approximately 1% of all cases of tuberculosis and 50% of these involve the spine. Intramedullary involvement is rare in tuberculosis. Clinical presentation of spinal intramedullary tuberculosis (SIMT) is similar to intramedullary spinal cord tumor. Here, we report the case of a 49-year-old female with dull aching pain of both upper limbs of 1-week duration. On examination, she had no motor deficits. All the deep tendon reflexes were normal. The plantar responses were flexor bilaterally. Cervical spine imaging favored intramedullary tumor. She had partial relief of symptoms with steroid treatment. Repeat imaging done 1 month later revealed mild interval enlargement of the intramedullary lesions and multiple enlarged mediastinal and hilar nodes. Endoscopic ultrasound-guided fine-needle aspiration cytology of mediastinal nodes was suggestive of granulomatous inflammation. Hence, SIMT was considered as the probable diagnosis. The patient was started on antituberculosis therapy.
Keywords: tuberculosis; spinal; intramedullary; tuberculoma